Jangha (wall) surrounding the Garbhagriha of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The jangha (wall) surrounding the garbhagriha (sanctum sanctorum) of the Undeshwar Temple is extensively adorned with sculptures. The bhadras (central offsets) display divine figures, while the stambhas (buttresses) are carved with representations of ashta dikapalas (deities representing eight cardinal directions), surasundaris and apsaras (celestial damsels), musicians and dancers.